Proses Kreativitas pada Gambar Anak Usia Dini di TK A Santo Yusup II Bandung - Martien Roos Nagara (JURNAL RUPA, 2022)
Children have unique views and perceptions through their creativity when expressing their ideas, ideas, and imagination in a picture. However, it is often found that when children pour pictures, only certain objects come to mind such as mountains, trees, and rice fields, even though there are still many objects around them that they can express in the form of pictures. This research needs to be done as an inspiration in training children’s creative abilities in expressing their ideas through an image. This research was conducted to determine the creative process of drawing children in TK A Santo Yusup II Bandung. The research method used is descriptive qualitative with an action research sampling technique purposive. The result of this research is the creative process of children’s ability to capture an object created through external communication and internal communication. Children observe, respond to, and analyze interesting objects around them through the five senses during the learning process and can represent what they live in their intuition through pictures.Keywordscreative process, drawing, early childhood, kindergarten